A human rights approach to the WHO Model List of Essential Medicines. - Seuba, Xavier (World Health Organization, 2006)
Since the first WHO Model List of Essential Medicines was adopted in 1977, it has become a popular tool among health professionals and Member States. WHO's joint effort with the United Nations Committee on Economic, Social and Cultural Rights has resulted in the inclusion of access to essential medicines in the core content of the right to health. The Committee states that the right to health contains a series of elements, such as availability, accessibility, acceptability and quality of health goods, services and programmes, which are in line with the WHO statement that essential medicines are intended to be available within the context of health systems in adequate amounts at all times, in the appropriate dosage forms, with assured quality and information, and at a price that the individual and the community can afford. The author considers another perspective by looking at the obligations to respect, protect and fulfil the right to health undertaken by the states adhering to the International Covenant of Economic, Social and Cultural Rights (ICESCR) and explores the relationship between access to medicines, the protection of intellectual property, and human rights.